COMMON TREND OF ANTIBIOTICS USAGE IN A TERTIARY CARE HOSPITAL OF PESHAWAR, PAKISTAN - Khan, Mohammad Shoaib; Ahmed, Zahoor; Jehan, Shah; Zaman, Fasseh -uz-; Khan, Salim; Zaman, Safeer; Shah, Farid Ullah (Journal of Ayub Medical College Abbottabad, 2010)
Background: Antibiotics are used to eradicate the pre- and postoperative infections in surgical procedures and in all others medical cases. However, inappropriate and indiscriminate use of antimicrobial agents can potentially have a number of problems. The emergence of antimicrobial resistant bacteria, an increased number of patients experiencing adverse drug events, and increased drug-related cost have been documented. The objective of the study was to determine the trend of use of antibiotics and hospitalisation of patients in various units of a tertiary care hospital, to investigate practice variation of antimicrobial agents within the hospital, and to identify and document any opportunity for its improvement. Methods: A questionnaire containing relevant information about the study was prepared. Patients’ age, sex, diagnosis, duration of hospital stay and type of antibiotic used were recorded and analysed, with particular reference to antibiotic group and disease pattern, in 3 different treatment areas of Hayatabad Medical Complex (HMC), Peshawar, Pakistan, from July 2006 to June 2007. Results: During the period under report, a total of 519 patients were studied for their disease and the type of antibiotics used. The leading type of antibiotics reported were 3rd generation antibiotic used on 147 (28.33%) patients in the 3 units collectively, 1st generation 127 (24.47%), and penicillin 99 (19.08%), while macrolides were the least used. Conclusion: The available resources are needed to be effectively utilised, to minimise the hospital stay due to rational use of antibiotics, and to minimise burden of antibiotics on poor patients. Keywords: Antibiotic usage, Tertiary care hospital, Peshawar, Pakistan